2022
DOI: 10.1021/acs.iecr.2c00758
|View full text |Cite
|
Sign up to set email alerts
|

How Does Alkali Etching Work on the Polyamide Membrane to Obtain an m-Phenylenediamine-Based NF Membrane?

Abstract: Fully aromatic polyamide (PA) membranes have been studied as nanofiltration (NF) membranes for decades because of their good chemical stability, but most of the membranes suffered from poor permeability and high rejection for monovalent ions. In this paper, an m-phenylenediamine (MPD)-based NF membrane was prepared by alkali activation on a reverse osmosis (RO) membrane. Characterization revealed the different etching paths on RO membranes fabricated by different concentrations of monomers of interfacial polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Combined with the TFC performance, the TFC membranes with rougher PA surfaces have higher ion rejection and selectivity, whereas those with smooth surfaces do not. These results are consistent with previous reports that the rougher morphologies with nano-foamed features can result in remarkable improvements in salt rejection. , …”
Section: Resultssupporting
confidence: 93%
“…Combined with the TFC performance, the TFC membranes with rougher PA surfaces have higher ion rejection and selectivity, whereas those with smooth surfaces do not. These results are consistent with previous reports that the rougher morphologies with nano-foamed features can result in remarkable improvements in salt rejection. , …”
Section: Resultssupporting
confidence: 93%
“…The stability of PA-based membrane operating in alkaline conditions over the long term requires further research and improvement. Some research efforts have shown promise on developing alkali-resistant PA membranes, , which could address the stability challenge and promote the application of PA-based membranes in electrochemical flow systems.…”
Section: Resultsmentioning
confidence: 99%
“…39 In general, for the fabrication of NF surface ultrathin via an interfacial polymerization process, two systems, that is, piperazine-trimesoyl chloride (PIP-TMC) and m-phenylenediamine-trimesoyl chloride (MPD-TMC) can be adopted. 40,41 The PIP-TMC system will offer a large water permeation flux, but the rejection of monovalent ions is ineffective; for the MPD-TMC system, the case is just the reverse. Therefore, with respect to the desirable water permeation flux and monovalent ion rejection, the tradeoff of above-mentioned two systems had better be seriously considered.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for the fabrication of NF surface ultrathin via an interfacial polymerization process, two systems, that is, piperazine‐trimesoyl chloride (PIP‐TMC) and m ‐phenylenediamine‐trimesoyl chloride (MPD‐TMC) can be adopted 40,41 . The PIP‐TMC system will offer a large water permeation flux, but the rejection of monovalent ions is ineffective; for the MPD‐TMC system, the case is just the reverse.…”
Section: Introductionmentioning
confidence: 99%